2020
DOI: 10.3390/agriculture10070301
|View full text |Cite
|
Sign up to set email alerts
|

Ecological and Economic Indicators for the Evaluation of Almond (Prunus dulcis L.) Orchard Renewal in Sicily

Abstract: Globally, almond production is experiencing a growing trend thanks to a strong interest in the health, gastronomic, and industrial properties that are linked to the fruits and their derivatives. After a constant and marked decline in the second half of the last century, the Mediterranean Basin is thoroughly reassessing this crop, which provides significant results with a modern orchard management. The opportunity determined by the transition from traditional to modern systems have increased the interest in eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 55 publications
1
23
0
Order By: Relevance
“…To better use these matrices, it would be appropriate to produce a formulated edible extract in order to improve its physicochemical and technological characteristics (solubility, palatability, manageability, stability) and to make it an ideal candidate for the production of health products with potential nutraceutical activity. This could make it possible to further enhance the value of by-products, maintaining a strong relationship with Mediterranean cultivars, which have great outcomes in terms of product healthiness [ 7 ]. To achieve this goal, we developed an acetonic almond skins extract (ASE) complex (CD-ASE), starting from a shell co-product of the Sicilian almond industry, and beta-cyclodextrin (CD), to increase the ASE stability, solubility, dissolution rate and biological activity.…”
Section: Introductionmentioning
confidence: 99%
“…To better use these matrices, it would be appropriate to produce a formulated edible extract in order to improve its physicochemical and technological characteristics (solubility, palatability, manageability, stability) and to make it an ideal candidate for the production of health products with potential nutraceutical activity. This could make it possible to further enhance the value of by-products, maintaining a strong relationship with Mediterranean cultivars, which have great outcomes in terms of product healthiness [ 7 ]. To achieve this goal, we developed an acetonic almond skins extract (ASE) complex (CD-ASE), starting from a shell co-product of the Sicilian almond industry, and beta-cyclodextrin (CD), to increase the ASE stability, solubility, dissolution rate and biological activity.…”
Section: Introductionmentioning
confidence: 99%
“…Given the fact that the bioactive compounds from almond and its by-products are highly influenced by environmental conditions, rational approaches should be developed to increase the biosynthesis of these compounds. With the aim of promoting an environmental-friendly stimulation of bioactive compounds production, different authors have already revealed that irrigation regime plays a dual role on almond production, since water constitutes the main resource employed during almond production, accounting for the 45.8% of the environmental impact associated with this procedure [3]: on one hand, sustained deficit irrigation constitutes a paramount strategy to ensure a proper water management in wide areas involved in almond production, as it the case of semi-arid Mediterranean regions [117]; on the other hand, such limited water regime may drive to an improvement of physical and sensory parameters of almond fruits, as well as increasing the biosynthesis of bioactive compounds (especially naringenin 7-O-glucoside and isorhamnetin-3-O-rutinoside), as already reported for AHs, which exhibited an increase in the irrigation-mediated production of phenolic compounds, and ASKs, mostly influenced by the agro-climatic conditions [20]. As a result, water management has been revealed as a critical factor related to the sustainability of almond production, with a higher significance in arid regions, which represent the most prevalent production areas worldwide.…”
Section: Sustainability and Future Perspectives For Almond Revalorizationmentioning
confidence: 99%
“…Among the countless almond varieties and cultivars, the Mission, Nonpareil, and California contribute up to 90% of the current worldwide production [2]. The data from the Food and Agriculture Organization (FAO) indicates that over 3 million tons of almond fruits are yearly produced throughout an area of over 2 million ha, being USA (78%), specifically California, Australia (8%), and Spain (6%) the largest producers [3]. Besides fruits, almond production involves the generation of several by-products that are normally discarded, accounting 0.8-1.7 million tons for shells and more than 6 million tons for almond hulls [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…In this context, a steady growth of preference for almonds from Italy has been observed (2). There are many and different causes that have led to this revaluation; among them certainly the recent contribution of the research in terms of agronomic advances, the reduction of the production area in the USA and the evolution of international markets and consumption on the domestic market (3). In Italy, a country with a strong vocation for almond cultivation, a large part of the total production can be attributed to Sicily.…”
Section: Introductionmentioning
confidence: 99%